ANALISA GETARAN POROS POMPA SENTRIFUGAL PADA SISTEM PENYAMBUNGAN KOPLING SABUK DENGAN VARIASI DIMENSI UKURAN TEBAL DAN LEBAR SABUK - Can, Aldo; Isranuri, Ikhwansyah (Universitas Negeri Surabaya, 2024)
Pump machines at the Regional Drinking Water Company can pump and deliver drinking water to homes for the community's needs. But in reality, pumping machines are not always 100% able to convert electrical energy into motion energy. The remnants of wasted energy are Vibration. Vibration can damage the engine components connecting to the pump, namely bearings, shafts and flanges. Another cause is misalignment in the flange connection of the motor and pump. The solution is to connect the two flanges with a flexible and elastic material, namely 4 belts. For this reason, this analysis uses the Spring Mass Model with a Multiple Degrees of Freedom System, which is 3 DOF. The thickness variations of the belt used are 4.5 mm, 6 mm and 7.5 mm and the width is 98 mm, 120 mm, and 145 mm. The results of the analysis of the belt with dimensions of 145 mm wide and 7.5 mm thick have the smallest acceleration, velocity, deviation values, namely 8.53 m⁄s2 , 0.42 m/s, 0.24 m, have mass, stiffness and the largest attenuation, which is 1.52 kg, 133 N/m, and 937.76 N⁄(m⁄s) and at Natural Frequency which is 7.5 mm thick, it means the best and most resistant among all variations of the thickness and width of the belt tested. and recommended to the Regional Water Company.